Superconductivity up to 14.2 K in MnB4 Under Pressure - Zhe‐Ning Xiang; Ying‐Jie Zhang; Lu, Qing; Li, Qing; Li, Yiwen; Huang, Tianheng; Zhu, Yijie; Ye, Yongze; Sun, Jian; Hai‐Hu Wen (Advanced materials (Weinheim), 2025)
The discovery of superconductivity in 3d transition‐metal compounds with strong magnetism is interesting but rare. Especially for Mn‐based compounds, there exist only very limited materials that show superconductivity. Here, the discovery of superconductivity is reported with an onset transition temperature up to 14.2 K in a Mn‐based material MnB4, which is the highest value among the stoichiometric Mn‐based superconductors. By applying high pressure, the continuous suppression of a weak semiconducting behavior and the occurrence of superconductivity after ≈30 GPa are found. With further increasing pressure, the superconducting transition temperature (Tc) is gradually enhanced and reaches the maximum onset transition value of ≈14.2 K at 150 GPa. The synchrotron X‐ray diffraction data reveal the unchanged monoclinic (S.G: P21/c) symmetry but an unusual crossover of the lattice parameters b and c in a certain pressure region as confirmed by the theoretical calculation. The findings show a promising way to explore high Tc superconductivity by combining the 3d‐transition metal magnetic elements and light elements.